Test-Retest Reliability of Cardiorespiratory Parameters Assessed by Metamax3B During Walking in Persons with Stroke - M, Compagnat; Jc, Daviet; Cs, Batcho; A, Perrochon; Jy, Salle; R, David; S, Mandigout (Cardiology and Cardiovascular Medicine, 2021)
Introduction: No studies have explored the reliability of the test re-test of the portable respiratory gas exchange analyzer (Metamax3B) in stroke patients despite its increasing use in clinical research. The objective was to evaluate the test-retest reliability of the cardiorespiratory parameters measured by Metamax3B during walking at self-selected speed in individuals with stroke. Material and Methods: This study included stroke individuals able to walk without human assistance. The participants were equipped with the Metamax3B, calibrated and installed according to the manufacturer's recommendations. The parameters, i.e. oxygen uptake (VO2), oxygen uptake by weight (VO2.kg-1), carbon dioxide production (VCO2), respiratory exchange ratio (RER), expiratory flow rate (VE), tidal volume (VT) and respiratory frequency (BF) were measured twice during 6 minutes of walking at self-selected speed in tests performed 2 days apart. The test-retest reliability of these parameters was evaluated using Bland-Altman analysis. Results: Sixteen individuals with stroke sequelae were included (mean age 64.5±14.3 years). No significant difference was observed between the test retest measurements for all parameters except for RER (mean difference=0.02; p=0.01). The Bland Altman analyses showed a mean bias of less than 5% between the test retest measurements. Discussion and Conclusions: The reliability of the cardiorespiratory parameters measured by Metamax3B during walking at self-selected speed in individuals with stroke was high, which encourages the use of this device in this population.